COMPUTATION OF HYPERGEOMETRIC FUNCTIONS - LEWIS, DAVID; RASHDI, HISHAM (مجلة العلوم الإنسانية والتطبيقية, 2017)
This research explored some methods for computing the hypergeometric function which can in some cases be difficult to find quickly and accurately. It have found that some softwares, such as Maple are of little use in such instances. So, in this case, this research highlights a method to compute a special case of the hypergeometric function which is in a very fast time compared with the Maple.